Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Product liability in an age of development risks : should South Africa reconsider adopting a development risk defence? - Tennant, Sarah-lynn; Van Heerden, C. M. (Corlia) (Journal of African Law, 2024)
To provide protection against harm caused by defective, unsafe products and to promote product safety, the law of product liability has developed as a specialized area of the law of delict (tort). The vexing question is, who should bear such liability? This contribution interrogates the notorious EU development risk defence, which exonerates manufacturers that meet certain stringent requirements for undiscoverable development risks in products that consequently inflict harm on consumers. In particular, it considers the election by South Africa, which recently adopted a “strict” product liability regime with the introduction of the Consumer Protection Act 2008, not to adopt such a defence. The purpose of this contribution is to consider the nature and scope of the development risk defence as contained in article 7(e) of the European Union (EU) Product Liability Directive and to determine whether it was prudent for South Africa to steer clear of incorporating a similar defence in its new statutory product liability regime.
Keywords: Defective product; Developmental risk; Hybrid regime; Product liability; Strict liability

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

An overview of the extent of the powers of South African competition authorities in the regulation of price discrimination under the Competition Act 89 of 1998 in the context of digital transformation - Magau, Phemelo (PER / PELJ, 2024)
The purpose of the Competition Act 89 of 1998 as amended (the Competition Act) is, among others, to promote the efficiency, adaptability and development of the economy as well as to provide consumers with competitive prices and product choices. In line with this purpose, the Competition Act provides that a dominant firm is prohibited from engaging in price discrimination if such conduct will likely substantially prevent or lessen competition, which would be to the detriment of consumers. Notably, the Competition Act has established various bodies to regulate competition and act against any conduct prohibited by this Act in South Africa. These bodies include the Competition Commission, the Competition Tribunal, and the Competition Appeal Court. Notwithstanding the prohibition of price discrimination, the Competition Act does not expressly provide adequate enforcement tools for competition authorities to combat uncompetitive practices in the digital era. Moreover, the Competition Act does not expressly grant these statutory bodies clear roles and mandates on providing consumers with adequate and suitable redress when they have been victims of algorithmic price discrimination. With recent technological developments, electronic commerce (e-commerce), and digital transformation, consumers have become vulnerable to various challenges such as excessive pricing, data breaches and algorithmic pricing. The online and digital markets are characterised by complex transactions, innovative technologies and business practices which expose all consumers, including vulnerable consumers, to different risks. As such, the role of the competition authorities needs to be recalibrated to enhance consumer protection on the pricing of goods and services. To this end this paper seeks to investigate the role and ambit of the powers of these competition authorities in the regulation of price discrimination in the context of digital transformation and the digital economy. This is done to assess whether the competition authorities have the necessary tools of enforcement to ensure that markets are competitive and to combat uncompetitive conduct in the digital economy and online markets.
Keywords: Algorithmic pricing; Competition authorities; Consumer protection; Digital transformation; Price discrimination

Overview of the role of selected consumer protection bodies in the regulation of prices and access to redress under the Consumer Protection Act 68 of 2008 - Magau, Phemelo; Chitimira, Howard (Acta Universitatis Danubius. Juridica, 2024)
The Consumer Protection Act 68 of 2008 (CPA) seeks to promote the achievement and maintenance of a fair, accessible, efficient, sustainable and responsible market place for consumer products and services in South Africa. Moreover, the CPA seeks to provide an accessible, consistent, harmonised, effective and efficient system of redress for consumers. Notably, the CPA provides that the supplier should not supply or enter into an agreement to supply any goods or services at a price that is unfair, unreasonable, or unjust. This is generally aimed at combating any problems that are suffered by consumers when accessing goods and services in South Africa. Accordingly, various regulatory bodies and related role-players were established to enforce consumer rights and provide redress mechanisms to vulnerable and affected consumers. These consumer protection bodies and related roleplayers include the National Consumer Commission (NCC), the National Consumer Tribunal (NCT), provincial consumer courts, ordinary courts and other alternative dispute resolution agencies. These bodies and role-players are statutorily obliged to resolve consumer disputes in South Africa. However, there are some uncertainty challenges regarding the jurisdiction of ordinary courts and consumer protection regulatory bodies in relation to disputes that relate to the consumers’ right to fair, just and reasonable prices, terms and conditions of goods and services. This article discusses the role of the NCC, the NCT, provincial consumer courts, ordinary courts and other alternative dispute resolution agencies in the regulation of prices for goods, services and access to redress for affected consumers under the CPA. This is done to provide some recommendations that could resolve jurisdictional and regulatory challenges in relation to the price and access to goods and services under the CPA.
Keywords: Consumer Protection Act 68 of 2008 (CPA); Consumer protection; Consumer rights; Prices; Regulatory bodies; Vulnerable consumers